2013
DOI: 10.1108/jmp-12-2012-0398
|View full text |Cite
|
Sign up to set email alerts
|

Virtual harassment: media characteristics' role in psychological health

Abstract: PurposeUsing the stressor‐strain model and media richness theory, this study seeks to investigate the relationship between receiving a harassing message via computer‐mediated communication and psychological health.Design/methodology/approachA sample of 492 individuals completed an online questionnaire. Three media characteristics are examined as potential moderators: media richness, anonymity of the harasser, and location where the victim received the harassing message.FindingsThe results suggest that virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 52 publications
1
56
0
Order By: Relevance
“…Coyne et al (2016) suggest that the boundaryless nature of cyberbullying may lead to a more severe impact because cyberbullying acts can quickly be distributed to everyone within an organisation. Furthermore, Ford (2013) found that perpetrator anonymity amplified the association between virtual harassment and fear of future harassment. The value of the WCM lies in its ability to investigate whether these unique features moderate the relationship between cyberbullying and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coyne et al (2016) suggest that the boundaryless nature of cyberbullying may lead to a more severe impact because cyberbullying acts can quickly be distributed to everyone within an organisation. Furthermore, Ford (2013) found that perpetrator anonymity amplified the association between virtual harassment and fear of future harassment. The value of the WCM lies in its ability to investigate whether these unique features moderate the relationship between cyberbullying and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, workplace bullying has occurred "at work" but perpetrators and targets do not need to be physically co-located for cyberbullying to occur. This allows perpetrators to send communications whenever they please and it can facilitate anonymity which is the extent that a perpetrator's identity is concealed (Ford, 2013). Anonymous cyberbullying can occur within the working context as employees can create fake email accounts or use pseudonyms to disguise their identity (D'Cruz & Noronha, 2013).…”
Section: Understanding and Defining Workplace Cyberbullyingmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, cyberbullying has been shown to negatively affect victims; including anxiety, job dissatisfaction, intention to leave and general well-being (Baruch 2005;Coyne et al 2017;Ford 2013).…”
Section: Introductionmentioning
confidence: 99%